2021
DOI: 10.3389/fcomm.2021.627316
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complexity of the L2 Intonation System: An Acoustic and Eye-Tracking Study

Abstract: Phonological research has demonstrated that English intonation, variably referred to as prosody, is a multidimensional and multilayered system situated at the interface of information structure, morphosyntactic structure, phonological phenomena, and pragmatic functions. The structural and functional complexity of the intonational system, however, is largely under-addressed in L2 pronunciation teaching, leading to a lack of spontaneous use of intonation despite successful imitation in classrooms. Focusing on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…It is also defined from different perspectives and with different focuses. Some scholars emphasized the pragmatic meaning and phrasal structure while others highlighted intonation patterns or tones (Liu & Reed, 2021). For Wells (2006, p. 1), it is the "study of how the pitch of the voice rises and falls and how the speakers use this pitch variation to convey linguistic and pragmatic meaning".…”
Section: Efl Intonation Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also defined from different perspectives and with different focuses. Some scholars emphasized the pragmatic meaning and phrasal structure while others highlighted intonation patterns or tones (Liu & Reed, 2021). For Wells (2006, p. 1), it is the "study of how the pitch of the voice rises and falls and how the speakers use this pitch variation to convey linguistic and pragmatic meaning".…”
Section: Efl Intonation Productionmentioning
confidence: 99%
“…Such structural and functional complexity of the intonation system, however, is largely undervalued or even forgotten in second/foreign language (SL/FL) pronunciation pedagogy (Liu & Reed, 2021, p. 1) which put more emphasis on the accurate production of isolated sounds or words, resulting in a lack of sufficient opportunities to practice intonation and a lack of spontaneous use of its patterns despite successful imitation in language classrooms. Thus, empirical studies on developing SL/FL intonation production are urgently needed (Hsieh, Dong, & Wang, 2013;Liu & Reed, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both Ghosh and Levis (2021) and Liu and Reed (2021) found L1 and L2 differences. The former identified a lower baseline and greater variation related to lexical stress errors in L2 listeners compared to L1 listeners.…”
mentioning
confidence: 90%
“…This brings me to Liu and Reed (2021). As they indicate, the signaling of contrastive and implicational information by Mandarin-English L2 speakers relies more on the acoustic feature of intensity, while L1 English speakers use pitch range, pitch level, and duration.…”
mentioning
confidence: 98%
“…Particularly in the domain of tone languages, only few studies have examined the acquisition of L2 intonation by L1 speakers of a tone language (He et al, 2012;Yuan et al, 2018;Liu and Reed, 2021;Shang and Elvira-García, 2022). These studies revealed effects of L2 proficiency and cross-linguistic differences, but very few studies have provided direct comparisons between learners whose L1 is a tone language versus learners whose L1 is a non-tone language.…”
Section: Introductionmentioning
confidence: 99%